2003
DOI: 10.1159/000072290
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Crystallographic and Theoretical Studies of an Anticonvulsant Enaminone: Methyl 4-(4’-Bromophenyl)amino-6-methyl-2-oxocyclohex-3-en-1-oate

Abstract: Objective: The aims of this study were to establish the structure of the potent anticonvulsant enaminone methyl 4-(4′-bromophenyl)amino-6-methyl-2-oxocyclohex-3-en-1-oate (E139), and to determine the energetically preferred conformation of the molecule, which is responsible for the biological activity. Materials and Methods: The structure of the molecule was determined by X-ray crystallography. Theoretical ab initio calculations with different basis sets were used to compare the energies of the different enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The enaminones E118, E139 and E169 were synthesized for this study according to methods reported previously (Edafiogho et al ., 1992, 1994, 2003). Briefly, the condensation reaction between β ‐diketo intermediates and appropriate amino compounds, under carefully controlled reaction conditions, yielded the enaminones E118, E139 and E169 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enaminones E118, E139 and E169 were synthesized for this study according to methods reported previously (Edafiogho et al ., 1992, 1994, 2003). Briefly, the condensation reaction between β ‐diketo intermediates and appropriate amino compounds, under carefully controlled reaction conditions, yielded the enaminones E118, E139 and E169 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…We tested the hypothesis that enaminones may interact with glutamate and/or its receptors to produce the reported anticonvulsant effects in rats and mice (Edafiogho et al ., 1992; Abou‐Zeid & Edafiogho, 2002). The rationale for this was based on the possible role of glutamate in the genesis of seizures (Dingledine et al ., 1990) as well as computer modeling of these compounds and crystallographic studies, which suggest that they would fit a putative glutamate receptor site (Abou‐Zeid & Edafiogho, 2002; Edafiogho et al ., 2003). In this study, we hereby report our findings on the effects of three enaminones on pure NMDA and non‐NMDA receptor‐mediated responses recorded in neurons of the nucleus accumbens (NAc).…”
Section: Introductionmentioning
confidence: 99%
“…The enaminone E139 was synthesized in house, characterized [1,32] and dissolved in dimethyl sulphoxide. Stock solutions of 10 m M were prepared, aliquoted and stored at -20 ° C and used within 3 weeks.…”
Section: Chemicals and Drugsmentioning
confidence: 99%
“…The activity of enaminones against NMDA receptor‐mediated responses, suggest that they can suppress the initiation of seizures as well as abort ongoing seizures fueled by the involvement of NMDA receptors activated by intense depolarization of neurons 55. The similarity in effect against these two distinct glutamate receptor subtypes also suggests that enaminones are unlikely to interact directly with glutamate receptors although modeling and X‐ray crystallographic predictions suggest that the enaminone pharmacophore could interact with a glutamate site 56. Detailed pharmacological characterization tested the hypothesis that anticonvulsant enaminones depressed EPSCs indirectly by employing intermediate synaptic modulators.…”
Section: Cellular Mechanisms Of Action Of Anticonvulsant Enaminonesmentioning
confidence: 99%